2000
DOI: 10.1016/s0038-1098(99)00532-3
|View full text |Cite
|
Sign up to set email alerts
|

Charge density wave formation accompanying ferromagnetic ordering in quasi-one-dimensional BaIrO3

Abstract: The magnetic, transport, optical, and structural properties of quasi-one-dimensional BaIrO 3 show evidence for the simultaneous onset of electronic density wave formation and ferromagnetism at T c3 175 K: Two additional features in the chain direction dc conductivity show a sudden change to metallic behavior below T c2 80 K and then a Mott-like transition at T c1 26 K: Highly non-linear dc conductivity, optical gap formation at Ϸ9k B T c3 , additional phonon modes, and emergent X-ray satellite structure suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
144
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(166 citation statements)
references
References 21 publications
21
144
1
Order By: Relevance
“…It is the first known ferromagnetic insulator with T c ≈ 180 K among the 5d TMOs [17]. Detailed studies on single crystals revealed a charge-density-wave (CDW) formation below the ferromagnetic order [18,51]. Recent experimental [52] and theoretical [53] investigations further revealed it as an exotic spin-orbit Mott insulator that is of great current research interest.…”
Section: Bairomentioning
confidence: 99%
See 3 more Smart Citations
“…It is the first known ferromagnetic insulator with T c ≈ 180 K among the 5d TMOs [17]. Detailed studies on single crystals revealed a charge-density-wave (CDW) formation below the ferromagnetic order [18,51]. Recent experimental [52] and theoretical [53] investigations further revealed it as an exotic spin-orbit Mott insulator that is of great current research interest.…”
Section: Bairomentioning
confidence: 99%
“…The sample should be cooled down slowly for the last sintering in order to ensure an oxygen stoichiometry [54]. Single crystals have been reported to grow out of the BaCl 2 flux at a relatively low temperature of 1,000 K [18]. HPHT synthesis is needed for all the other polytypes [19,21,55,56].…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…This conventional wisdom conflicts with two trends observed among layered iridates such as the Ruddlesden-Popper phases, Sr n+1 Ir n O 3n+1 (n = 1 and 2; n defines the number of Ir-O layers in a unit cell) [1-5] and hexagonal BaIrO 3 [6]. First, complex magnetic states occur with high critical temperatures but unusually low ordered moments.…”
Section: Introductionmentioning
confidence: 97%